Danger Indicators of Natural Radionuclides in Consumed Products in the City of Hilla Markets - Alghazaly, ‪Saif M. (Iraqi Journal of Science, 2025)
Many products contain several natural radionuclides in their composition. Frequent use of these products increases the cumulative radiation risk. This study aimed to measure the radioactivity using NaI (Tl)detector of consumer products found in local markets that contain natural radioactive materials (NORMs) and are used for various purposes. Average specific activity values are 3.52 Bq/kg for Uranium-238, 15.77 Bq/kg for Thorium-232, and 153.53 Bq/kg for Potassium-40. The radium equivalent (Raeq) was determined to be 45.22, and the average internal and external absorbed doses for the study samples were 39.77 and 21.21 nGy/h, respectively. The average values of the measured external and internal risk indexes are 0.12 and 0.13, and the representative level index is about 0.33. The study results were compared to global averages, according to the United Nations Scientific Committee on the Effects of Atomic Radiation (UNSCEAR) and the International Commission on Radiological Protection (ICRP); the study determined that the levels of proven health risks in consumer products are safe and unlikely to pose a significant threat to the public.